Automotive Wastes. (1st October 2015) - Guigard, Selma E.; Shariaty, Pooya; Niknaddaf, Saeid; Lashaki, Masoud Jahandar; Atkinson, John D.; Hashisho, Zaher
Abstract : A review of the literature from 2014 related to automotive wastes is presented. Topics include solid wastes from autobodies and tires as well as vehicle emissions to soil and air as a result of the use of conventional and alternative fuels. Potential toxicological and health risks related to automotive wastes are also discussed.